Urgensi Laporan Penelitian Kemasyarakatan Dalam Penjatuhan Pidana Bagi Anak Pelaku Tindak Pidana - Patty, Mercy Pratiwi; Hehanussa, Deassy Jacomi Anthoneta; Wadjo, Hadibah Zachra (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: Reality shows that crimes are not only committed by adults, but also by children. Children who commit crimes must be held accountable for their actions that violate the law. Purposes of the Research: In order to analyze the juvenile offender, the law enforcement and sentencing process applied to the child is carried out specifically by prioritizing the best interests of the child. Methods of the Research: Type of research: Juridical Empirical, Data Sources include primary data and secondary data. Techniques for reviewing and collecting primary and secondary data are using literature studies and interview results. Data analysis used in legal research is qualitative analysis. Results Originality Findings of the Research: Based on the results of the study, it was found that the urgency of a community research report in imposing sanctions on children who commit criminal acts is an important matter. Community research reports that are made basically have an influence on the judge's decision in juvenile court. With the availability of community research reports, it can be used as consideration for judges in making their decisions as regulated in Article 60 Paragraph (3) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Furthermore, if the judge does not consider the community research report from the Community Counselor, the legal consequences arising from the decision on the child who commits the crime are null and void, as referred to in Article 60 Paragraph (4) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.